Business Value of Digitization: Curse or Blessing? - Dekkati, Sreekanth; Thaduri, Upendar Rao; Lal, Karu (Global Disclosure of Economics and Business, 2016)
Converting something from analog to digital form is called "digitization." Another name for this process is "digital enablement." To phrase it another way, digitization is converting an analog process into a digital form without making any changes to the analog process itself that are distinct. The research presents a concise history of digitization on a global scale, focusing on its influence on business research, the difficulties associated with assuring digital service quality, the contribution of digital transformation and mobilization to the scientific and business world, and evidence of the increasing importance placed on digital transformation.